Analysis of the Learning Process and Learning Outcomes of Mathematics for Class VIII UPTD SMP Negeri 1 Gunungsitoli Idanoi - Nur Ayu Zebua; Amin Otoni Harefa; Yulisman Zega (CV. Rayyan Dwi Bharata, 2023)
The background of this research is the researcher's observations about the learning process and learning outcomes that occur at UPTD SMPN 1 Gunungsitoli Idanoi. This study intends to obtain information or a clear picture of how the learning process is carried out in this school with the learning outcomes achieved by class VIII students. This type of research is a qualitative research using a descriptive approach research method. The research population was all students of class VIII which consisted of seven classes with twenty students in each class. Data was collected through interviews, documentation, observation of the learning process. Then, it is analyzed by the percentage of the learning process and learning outcomes presented in tabular form. The data analysis used consisted of data collection, data presentation, data triangulation, and conclusions. Based on the results of the research that has been done, the average percentage of observations of the learning process is 74.01% which is quite good with an average learning result of 73.98 which is quite satisfactory.